Effect Of Spraying With GOFARSEAWEED and SPRINT ALGA Extracts On Growth And Production Of Cucumbers In Field Agriculture - شيخ سليمان نصر; الأحمد جمال; جعفر فاطمه محمود (Latakia University Journal -Biological Sciences Series, 2021)
The research was carried out during spring season 2020 within an agricultural field in Al-shire village to study the effect of some seaweed extracts on the vegetative growth and production of cucumber . Hybrid cucumber ,PRINCE, and two types of seaweed extracts were used in agriculture. The study included (5) treatments(control plants sprayed with water , plants sprayed with go far seaweed extract at a concentration of( 0.5g/l and 1g/l) , plants sprayed with sprint alga extract at a concentration of (1m/l and 2m/l)) and (4) replications for each treatment according to the design of complete random sectors .The results showed that foliar spraying with seaweed extracts achieved an increase in stem length ,number of branches and leaf surface area ,with significant differences compared to the control . Foliar spray treatments with seaweed extracts also outperformed the number of female flowers and fruits formed on the plant ,as the treatment of foliar spray with GOFARSEAWEED extract a concentration of 1g/l gave the highest number of female flowers ,which reached (82)flowers/plant ,and the largest number of fruits which reached (37) fruits/plant .The GOFARSEAWEED extract at a concentration of 1g/l and SPRINT ALGA at a concentration of 2ml/l gave the largest yields per unit area of 4625 g/m2 , 4375 g/m2 respectively .